When Inertia Generates Political Cycles - Raphäel Soubeyran (Fondazione Eni Enrico Mattei (FEEM), 2006)
We propose a simple infinite horizon of repeated elections with two candidates. Furthermore we suppose that the government policy presents some degree of inertia, i.e. a new government cannot completely change the policy implemented by the incumbent. When the policy inertia is strong enough, no party can win the election a consecutive infinite number of times.
Keywords: D72; H7; 330; Political Cycles; Inertia; Politischer Konjunkturzyklus; Wahl; Theorie